Detecting requirements defects with NLP patterns: an industrial experience in the railway domain - Ferrari, Alessio; Gori, Gloria; Rosadini, Benedetta; Trotta, Iacopo; Bacherini, Stefano; Fantechi, Alessandro; Gnesi, Stefania (Empirical software engineering : an international journal, 2018)
In the railway safety-critical domain requirements documents have to abide to strict quality criteria. Rule-based natural language processing (NLP) techniques have been developed to automatically identify quality defects in natural language requirements. However, the literature is lacking empirical studies on the application of these techniques in industrial settings. Our goal is to investigate to which extent NLP can be practically applied to detect defects in the requirements documents of a railway signalling manufacturer. To address this goal, we first identified a set of typical defects classes, and, for each class, an engineer of the company implemented a set of defect-detection patterns by means of the GATE tool for text processing. After a preliminary analysis, we applied the patterns to a large set of 1866 requirements previously annotated for defects. The output of the patterns was further inspected by two domain experts to check the false positive cases. Additional discard-patterns were defined to automatically remove these cases. Finally, SREE, a tool that searches for typically ambiguous terms, was applied to the requirements. The experiments show that SREE and our patterns may play complementary roles in the detection of requirements defects. This is one of the first works in which defect detection NLP techniques are applied on a very large set of industrial requirements annotated by domain experts. We contribute with a comparison between traditional manual techniques used in industry for requirements analysis, and analysis performed with NLP. Our experience shows that several discrepancies can be observed between the two approaches. The analysis of the discrepancies offers hints to improve the capabilities of NLP techniques with company specific solutions, and suggests that also company practices need to be modified to effectively exploit NLP tools.